Miniaturized underwater fishbone–slot integrated patch array antenna for freshwater applications - Daud, Nor H.; Ismail, A.; Sali, A.; Ismail, Mohd H. (Taylor's University, 2024)
The size restrictions present a significant issue when designing antennas for underwater applications that use electromagnetic (EM) waves for communication. Underwater antenna become complex and challenging to manufacture in addition to having bulk and weight issues. Additionally, it is impractical to establish wireless sensor networks underwater due to the high antenna size. To address this issue, this paper investigates and develops a proposed underwater antenna that consists of 1  2 linear Rectangular Microstrip Patch Array Antennas (RMPAAs) integrated with a fishbone-shaped slot and rounded corner based on a truncated ground plane and a T-shaped slot structure. The simulated results offered noteworthy compatibility with the measured results. The proposed antenna array has achieved better performance than other underwater antennas recently published in scientific journals in terms of return loss, bandwidth, and antenna dimensions. The antenna shows high performance, including an impedance bandwidth of 400 MHz (43.3%) at operating frequency of 921 MHz and a return loss magnitude of 30.0 dB (around 53.3%), especially in comparison to the previously reported designs of 14.0 dB. The overall dimensions of the proposed underwater antenna are 54 × 43 mm2 with a finite ground plane of 25  43 mm2. Meanwhile, the total area of the proposed antenna was minimized by 2322 mm2 (around 96.0%), especially in comparison to the previously reported designs of 58000 mm2. The findings indicate that the proposed underwater antenna is well suited for safety device applications. The critical challenges have also been identified and addressed in this research.